The failure to respond to changes in the road environment: Does road familiarity play a role?. (August 2018) - Martens, Marieke H.
Highlights: Clearly visible and relevant information does not always lead to a response. Expectations and road familiarity do not completely explain the failure to respond. Road layout itself also seems to trigger expectations. In-car message leads to best response, better than additional road signs. Abstract: Road signs do not necessarily lead to the right response. Especially when signs are changed, drivers may not always detect new signs and may therefore fail to respond correctly to the situation indicated. The present driving simulator study investigated whether road familiarity (increased exposure to the same road) influenced failure to respond to a change in road signs. In order to study the failure to respond, participants were presented with a change in the road lay-out (as indicated by a road sign) in the last of a series of simulated drives. The change introduced was the conversion of a normal road into a No-Entry road. Results show that several participants failed to respond to this change. However, the failure to respond was not simply the result of familiarity with the road or prior exposure to precisely the same road, but seemed to be influenced by expectations induced by the road design. Additional safety measures such as the placement of additional road signs reduced the failure to respond. An auditory in-vehicle message gave the best results. Interestingly, both in the case of additional signs and of the in-vehicle message, a general warning was sufficient, without the need to specify the precise traffic situation.